Performance appraisal satisfaction and turnover intention: the mediating role of work engagement - Memon, Mumtaz Ali; Salleh, Rohani; Mirza, Muhammad Zeeshan; Cheah, Jun Hwa; Ting, Hiram; Ahmad, Muhammad Shakil (Emerald, 2020)
Purpose: The purpose of this paper is to examine the impact of performance appraisal satisfaction (PAS) on work engagement (WE) and the impact of WE on turnover intention. Furthermore, this paper investigates the mediating effect of WE between PAS and turnover intention. Design/methodology/approach: The sample consisted of employees of 12 oil and gas organisations operating in Malaysia. The data collection process consists of two surveys using a three-month time lag approach. A total of 295 samples were used for the final data analysis. Partial least squares structural equation modelling was performed to test the research hypotheses. Findings: The results indicate a strong causal relation between PAS, WE and turnover intentions. In brief, PAS was found to be a predictor of WE, and WE has a negative impact on employees’ turnover intention. Furthermore, WE proved to be a mediator between PAS and turnover intentions. Practical implications;The findings of this study can be used as a basis to consider PAS to increase employees’ level of WE and to decrease voluntary turnover. Overall, the findings provide pragmatic insights for human resource management practitioners and relevant stakeholders. Originality/value: To date, little is known about the interrelationship between PAS, WE and turnover intention. Importantly, the mediating role of WE between PAS and turnover intention has remained unexplored. This study fills this gap in the existing literature.